GENOMIC ANALYSIS TO ELUCIDATE THE ANTIBIOTIC RESISTANCE MECHANISM OF EXTREMELY DRUG-RESISTANT PSEUDOMONAS AERUGINOSA STRAINS ISOLATED FROM BANGLADESH - Zahra, Fatimah Az; Jabeen, Ishrat; Uddin, Mohammed Jafar; Nahar, Nazmun; Islam, Sohidul; Shuvo, Sabbir R (Bioresearch Communications, 2022)
Multidrug-resistant P. aeruginosa has potential to cause nosocomial infections. In this study, whole-genome sequencing was performed of two extremely drug-resistant novel strains SRS1 and SRS4 isolated from Bangladesh. The size of draft genome of SRS1 is 6.8 Mbp, and 7.0 Mbp for SRS4. In silico analysis predicted that the genome of SRS1 has 82 and SRS4 has 75 antibiotic-resistant genes (ARGs). Antibiogram results revealed that both SRS1 and SRS4 were resistant to multiple members of the antibiotic groups of β−lactam, quinolones, and aminoglycosides families. In addition, the genomes of both SRS1 and SRS4 were predicted to have multiple mobile elements like prophages and plasmids. Comparative genome analysis with wildtype PAO1 and another drug-resistant P. aeruginosa strain JNQH-PA57 revealed that SRS1 and SRS4 contain more antibiotic resistance genes like AAC (6´)-II, ANT (2´´)-Ia, ANT (3´´)-IIa, OXA-395, PME-1, qacEΔ1, tet(A), tet(D), VEB-9 than PAO1 and JNQH-PA57. This study shows the importance of the genomic study to understand the distribution of ARGs in Bangladeshi P. aeruginosa strains to demonstrate the mechanisms responsible for multi drug resistance. Bioresearch Commu. 9(1): 1208-1214, 2023 (January)